Electrochemical behavior of HAp/CNTs/316LSS coatings into simulated body fluid solution. Issue 4 (28th August 2018) - Thom, Nguyen Thi; Nam, Pham Thi; Phuong, Nguyen Thu; Huy, Nguyen Trung; Hong, Cao Thi; Van, Tran Thi Thanh; Hai, Nguyen Song; Dung, Pham Tien; Thanh, Dinh Thi Mai
Abstract: Hydroxyapatite (HAp) was known as a bone implant material due to its bio‐compatibility, bioactive, chemical stability and its compositional similarity to natural bone. In order to improve mechanical properties of pure HAp coatings, CNTs added into electrolyte to form HAp/CNTs coatings. The HAp/CNTs coatings were synthesized successfully on the surface of 316 L stainless steel (316LSS) by electrodeposition technique. In this work, electrochemical behavior of 316LSS and HAp/CNTs/316LSS in simulated body fluids (SBF) solution was investigated. SEM images present the formation of new apatite crystal on the materials after 21 days of immersion in SBF solution. The formation of coated apatite improved corrosion protection ability for 316LSS by the decrease of the corrosion current density and increase of impedance modulus during immersion process in SBF solution.